O ensino da arte nas prisões: desafios, possibilidades e limites para uma educação humanizadora - Martins , Valdir Borges (2017)
This research aims to analyze the teaching art from its humanizing dimension as school discipline offered to students in a situation of deprivation of liberty by checking the challenges and possibilities for such an offer. For this was directed a study of art from a concept that features its humanizing aspect, therefore, we were chosen as theoretical foundation Marxist aesthetics, to understand that Marxism, based on human historicity, provides us with a solid foundation for understanding humanism in order that we become more human as we become aware of our history. By linking art and humanization of education in prisons, it was decided by a study of public policies for this type of education, checking the challenges for the execution of this offer, the existing legislation, the applicability in education as a right and the possibility of reintegration social students attended in criminal units. After the conceptual analysis of art and understanding of the specificity of the prison as a potential educational space, there was the possibility of humanization of art and education itself that space. Will reflect also on the art of teaching concepts in Brazil, and on the practical universe of this teaching through the school's Pedagogical Political Project analysis with regard to the teaching of art. This work therefore presents challenges and opportunities related to themes: humanization, art, education and prison.